Development of scratch educational game-based learning media to improve students' problem-solving ability - Alhasir, Ahmad; Mariatun, Ika Lis (Asatiza: Jurnal Pendidikan, 2024)
This study develops Scratch educational game-based learning media to improve students' problem-solving skills in economics subjects regarding financial institutions in class X MA An-Nidhomiyah. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through questionnaires, observations, interviews, and tests, and analyzed descriptively. The research subjects were 16 grade X students. The results showed that this learning media was very feasible to use, with a validation score of 4.5 from the material expert, 4.6 from the teacher, and the media expert's assessment showed feasibility. In addition, this media is proven effective in improving students' problem-solving skills, with a Gain Score of 1.5 which is in the high category.